High Current Applications Issues in Designs of High Current Applications - Varecha, Patrik; Vavrus, Vladimir; Zuczek, Bretislav (Communications - Scientific letters of the University of Zilina, 2018)
This paper deals with design high current printed circuit boards (PCB), with the issues of implementation the power layer into standard PCB and influence of parasitic parameters of conductive traces of PCB. The parasitic parameters of conductive traces play a significant role in design of high current PCB, and therefore must be minimized. The technology of manufacturing PCB for high current designs as a compact device is mentioned in the paper. The quality of MOSFET switching power in high current design was compared in two ways of proposed leading power lines in order to demonstrate the influence of parasitic inductances of conductive traces.